Determinación del potencial de membrana mitocondrial mediante citometría de flujo durante el proceso de criopreservación de espermatozoides epididimarios de alpacas - Allauca, Pablo (2019)
The aim of this study was to demonstrate, by flow cytometry, that the percentage of alpaca spermatozoa with high mitochondrial membrane potential (MMP) is significantly reduced after the cryopreservation process. Forty-one alpaca testicles were obtained from a local slaughterhouse in the Ninacaca district, Pasco, Peru. The spermatozoa were recovered from the tail of the epididymis with an extender based on skim milk and only those samples with minimum 30% motility and 50x106 spermatozoa/ml were cryopreserved. The MMP evaluation was carried out before and after the cryopreservation process. Each sample was incubated for 10 minutes at 38 °C with MitoTracker Deep Red (100 nM) to determine the percentage of high MMP by imaging flow cytometry. The effect of cryopreservation on the percentage of spermatozoa with high MMP was evaluated by a paired t-student test and the percentage of motility and sperm with high MMP were correlated. A 49.82 ± 12.41 and 34.97 ± 9.96% of high MMP were obtained in samples before and after the cryopreservation process (p<0.05). A positive correlation was found (r = 0.62, p<0.0001) between motility and PMM. It is concluded that MMP is significantly reduced after the cryopreservation process, a parameter related to sperm motility.